Efeito angiogênico da aplicação de ondas de choques radiais na musculatura íntegra do quadríceps de ratos Wistar: uma nova perpectiva para fisiologia muscular - Rodrigo Santos Almeida (2020)
ABSTRACT Extracorporeal shockwave therapy (ESWT) was introduced in medical practice in the early 1990s as a derivation of urological lithotripsy. In the United States, the use of ESWT in the musculoskeletal system was approved in 2001, and in Brazil, in 1998. Currently it has been applied to treat various orthopedic pathologies (such as epicondylitis, patellar tendinitis, tendinosis, calcareous shoulder tendinitis, retardation. of consolidation, pseudoarthrosis of fractures, great trochanter bursitis, plantar fasciitis, various sports injuries) here are other indications being studied such as diabetic ulcers, neuromuscular spasticity, erectile dysfunction, coronary obstruction, chronic pelvic pain syndrome and aesthetic treatment as well as the use in muscles of healthy athletes showing improvement in elasticity and recruitment muscular. The present study evaluated the right quadriceps musculature of Wistar rats after shockwave application with the radial appliance Swiss Dolorclast Smart 20 (Electro Medical System) and compared with the same muscle group on the left side, which was not subjected to such waves. The experiment was carried out in the vivarium of the Faculty of Medicine of Barbacena - MG. Twelve Wistar rats were submitted to shockwave application under intraperitoneal anesthesia. The animals were submitted to three weekly interval applications, according to the protocol of the appliance model, and on the fourth week, under anesthetic deepening, the Wistar rats were euthanized and the quadriceps muscles were sent for comparative histological analysis in the Microscopy laboratory of the Faculty of Medicine of Barbacena and the Institute of Biological Sciences of the Federal University of Minas Gerais and reviewed in the TECSAR laboratory, located in Belo Horizonte. There was a slight increase in fibrovascular proliferation with the number of nuclei per fiber, presence of satellite cells and vessels with significant statistical difference (p < 0.005) on the quadriceps submitted to shockwave application in relation to the contralateral one, which demonstrated the capacity of angiogenesis in intact muscles by the method employed. Keywords: Shock waves. Angiogenesis. Integrated musculature.